Examen Especial al Componente Activos Fijos de la Empresa Pública- Empresa Municipal de Agua Potable y Alcantarillado Riobamba (Ep-Emapar) Periodo 2020. - Quishpi Quitio, Blanca Alicia (2023)
Controling the activities and procedures of private and public institutions has huge, importance, that is why the special test is a mechanism that allows directing the correct functioning and application of regulations of each one of the goods in the organizations. A non-experimental design was applied as there was no manipulation of variables, in addition, the documents that the company provided and the personnel who work in the accounting-financial area were used, as the size of the documentary population, which contributed to the research process. In the same way, techniques for gathering information were used, techniques such as interviews, surveys, direct observation, it was possible to collect data and information. An internal audit department that does not have enough personnel to carry out an adequate control in the use of fixed assets, is presented in the structural organization chart of the Company (EP-EMAPAR), where the following results could be obtained. Administrative assets in 2020 had a significant increase in furniture, machinery, equipment and vehicles accounts, while in 2019 these accounts had a value of $0. In addition, an increase in infrastructure assets was generated in the drinking water infrastructure accounts, representing 10%, and sewerage infrastructure, representing 101%. These results allowed us to verify the current state of the entity's fixed assets. Once the special examination to the fixed assets of EP-EMAPAR was completed, in the internal control sistema evaluation questionnaires were applied based on the norms of the General Comptroller of the State, resulting in a moderate confidence level of 73.33% and a moderate risk level of 26.67%, however, there are different shortcomings such as the absence of controls on the administration processes of institutional assets, absence of surprise controls on assets, lack of a plan to deregister the goods that are not operational, deficiency in the physical verifications also do not record the states (good, bad, regular) of the equipment and machinery. Therefore, as a control measure, it was determined to comply with the regulatory provisions stipulated in the NIC International Accounting Standards, and the Internal Control Standards of the State Comptroller General.